2002
DOI: 10.1080/07448480209603447
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Heart Disease Risk-Factor Screening Among Traditional College Students

Abstract: The author collected data on serum cholesterol, blood pressure, and self-reported health behavior in 226 college students aged 18 to 26 years. Twenty-nine percent had undesirable total cholesterol levels, 10% had high cholesterol, 10% had high systolic blood pressure, and 11% had high diastolic blood pressure. Half or more of the participants consumed a diet high in saturated fats, engaged in binge drinking, had a parental risk for high cholesterol or blood pressure, or reported they experienced elevated stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 34 publications
6
46
0
Order By: Relevance
“…Compared to older populations, younger populations, such as emerging adults, frequently consume foods high in fat (Anderson, Winett, Wojcik, & Williams, 2010;Huang et al, 1994;Spencer, 2002) with a higher percentage of kcal from total fat than the recommended guidelines (Hampl & Betts, 1995;Kronsberg et al, 2003;Lichtenstein et al, 1998). The frequency of eating fast food, which tends to be high in fat content, has been positively associated with fat intake among samples that included emerging adults (French, Story, Neumark-Sztainer, Fulkerson, & Hannan, 2001;Jenkins & Horner, 2005;Satia, Galanko, & Siega-Riz, 2004).…”
Section: Emerging Black Adults and Dietary Fat Intakementioning
confidence: 99%
See 4 more Smart Citations
“…Compared to older populations, younger populations, such as emerging adults, frequently consume foods high in fat (Anderson, Winett, Wojcik, & Williams, 2010;Huang et al, 1994;Spencer, 2002) with a higher percentage of kcal from total fat than the recommended guidelines (Hampl & Betts, 1995;Kronsberg et al, 2003;Lichtenstein et al, 1998). The frequency of eating fast food, which tends to be high in fat content, has been positively associated with fat intake among samples that included emerging adults (French, Story, Neumark-Sztainer, Fulkerson, & Hannan, 2001;Jenkins & Horner, 2005;Satia, Galanko, & Siega-Riz, 2004).…”
Section: Emerging Black Adults and Dietary Fat Intakementioning
confidence: 99%
“…Cartwright and colleagues (2003) found that teenage females had lower odds of consuming high-fat foods (56)(57)(58)(59)(60)(61)(62)(63)(64), p = .00) compared to males. Spencer (2002) found that females were less likely to eat diets high in saturated fats compared to males (χ² = 25.01, df = 3, p = .00). Harcrow (2010) found that males had significantly higher fat intake scores (M = 30.44, SD = 10.19, F = 10.71; p = .001) compared to females (M = 28.22, SD = 8.95).…”
Section: Gender and Dfimentioning
confidence: 99%
See 3 more Smart Citations